COHESION AND COHERENCE IN ENGLISH EDUCATION STUDENTS’ THESIS - Cut Irna Liyana (Englisia: Journal of Language, Education, and Humanities, 2014)
This study is entitled Cohesion and Coherence in English Education Students’ Thesis. The aim of this study is to describe the cohesion and coherence as wholeness aspect of discourse in English Education students’ thesis. This study is a qualitative research. The data sources in this study are the thesis of three students that were obtained by purposive sampling. Furthermore, analysis of the data was done by identifying and classifying the data that related to cohesion, based on the theory of Halliday and Hasan (1976), and related to coherence, based on the theory of Oshima and Hogue (1991). From analysis, it was found four things related to cohesion and coherence. First, the use of grammatical cohesion devices in thesis, which consists of reference, substitution, ellipsis, and conjunction; and the use of lexical cohesion devices, which consists of reiteration and collocation, was used in thesis. Second, the violence of cohesion device was found in grammatical devices, such as reference and conjunctions. Third, the use of coherence devices, which consists of key nouns repetition, use of pronouns, transition signal, and logical order of chronology was found in students’ thesis. Fourth, the cause of the error coherence of thesis consists of keyword repetition errors, inconsistent pronouns, inappropriate transition signal, grammatical errors, and inappropriate punctuation.